Genetic syndromes with localized subcutaneous fat tissue accumulation - Precone, Vincenza; Barati, Shila; Paolacci, Stefano; Salgarello, Marzia; Visconti, Giuseppe; Gentileschi, Stefano; Guerri, Giulia; Gagliardi, Lucilla; Aquilanti, Barbara; Matera, Giuseppina; Velluti, Valeria; Miggiano, Giacinto Abele Donato; et al. (Acta Biomedica Atenei Parmensis, 2019)
Syndromes with localized accumulation of subcutaneous fatty tissue belong to a group of genetically and phenotypically heterogeneous disorders. These diseases may show some common signs, such as nodular fat, symmetrical fat masses, obesity, fatigue, lymphedema and symmetrical lipomas (painful or otherwise). Other symptoms may be specific for the different clinical entities, enabling correct differential diagnosis. Disorders belonging to this spectrum are lipedema, generalized diffuse or nodular forms of Dercum disease, localized nodular Dercum disease and multiple symmetric lipomatosis. Here we summarize the genes involved in syndromes with localized accumulation of subcutaneous fat and the test we use for genetic analysis.